1997
DOI: 10.1046/j.1365-294x.1997.00287.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in Costa Rican populations of the tropical timber species Cedrela odorata L., assessed using RAPDs

Abstract: Cedrela odorata L. (Spanish cedar), an economically important timber species native to the American tropics, is the focus of increasing conservation concern due to high rates of deforestation within its native range. To assess the extent of the genetic diversity within and between populations of this species, samples were obtained from 10 widely dispersed populations within Costa Rica and analysed for random amplified polymorphic DNA (RAPD) variation. Fourteen 10‐mer primers were used to generate 97 polymorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
66
1
10

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 38 publications
(54 reference statements)
9
66
1
10
Order By: Relevance
“…The analysis of molecular variance indicated a total variance of 0.43456. This value is similar to that obtained by Gillies et al (1997) who analyzed Cedrela odorata populations in Costa Rica, with the same type of marker. High levels of total variance are also reported for temperate climate species (Yeh et al, 1995;Liao and Hsiao, 1998).…”
Section: Resultssupporting
confidence: 89%
“…The analysis of molecular variance indicated a total variance of 0.43456. This value is similar to that obtained by Gillies et al (1997) who analyzed Cedrela odorata populations in Costa Rica, with the same type of marker. High levels of total variance are also reported for temperate climate species (Yeh et al, 1995;Liao and Hsiao, 1998).…”
Section: Resultssupporting
confidence: 89%
“…28.8 in Pinus chiapensis and Syzygium travancoricum. Our results of polymorphism in primers (50-100 %) matched with earlier studies (Gillies et al, 1997;Kant et al, 2006) and showed that species diversity was not low and it should be able to fit in the environmental variation (Fu et al, 2003). Primer 3 and 5 gave single band, which might be explained as RAPD markers tag specific regions in the genome.…”
Section: Levels Of Polymorphismsupporting
confidence: 91%
“…Esses valores podem ser atribuídos à fragmentação das áreas em que foram obtidos, com forte pressão de seleção antrópica. A comparação com o índice de Shannon encontrado em outros estudos é limitada, pois abordagens diferentes podem ter sido utilizadas para calculá-lo (Gillies et al, 1997). Assim, os resultados observados, neste trabalho, podem contribuir para grupos de pesquisa que utilizem padrões similares.…”
Section: Resultsunclassified